2021
DOI: 10.3389/fcvm.2021.784715
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in the Pathogenesis of Arrhythmogenic Cardiomyopathy: Secondary Event or Active Driver?

Abstract: Arrhythmogenic cardiomyopathy (ACM) is a rare inherited cardiac disease characterized by arrhythmia and progressive fibro-fatty replacement of the myocardium, which leads to heart failure and sudden cardiac death. Inflammation contributes to disease progression, and it is characterized by inflammatory cell infiltrates in the damaged myocardium and inflammatory mediators in the blood of ACM patients. However, the molecular basis of inflammatory process in ACM remains under investigated and it is unclear whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 160 publications
0
8
0
Order By: Relevance
“…While in the last few years the possible role of inflammation in ACM onset and progression led to a significant number of publications, few detailed clinical studies on a large cohort of patients with “hot-phases” can be found [ 23 , 24 , 25 , 26 ]. We were able to select only 9 studies describing cohorts of patients affected with ACM who showed myocarditis-like episodes [ 5 , 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While in the last few years the possible role of inflammation in ACM onset and progression led to a significant number of publications, few detailed clinical studies on a large cohort of patients with “hot-phases” can be found [ 23 , 24 , 25 , 26 ]. We were able to select only 9 studies describing cohorts of patients affected with ACM who showed myocarditis-like episodes [ 5 , 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that inflammation, either reactive to internal influences or triggered by exogenous factors, has a role in the pathogenesis of ACM. In addition, most of the evidence on the role of inflammation and autoimmunity in this disease derives from studies on desmosomal forms of disease, while non-desmosomal, as well gene-elusive forms, require further studies to assess the role of inflammation and of possible modifier factors [ 23 , 24 , 25 , 26 , 33 ]. Studies on murine models supported the evidence that ACM inflammation can precede the onset of overt histological and electrical abnormalities [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiomyocyte loss is a fundamental pathological mechanism for triggering the infiltration of immune cells and innate inflammation of the myocardial tissue, itself. The considerably damaged myocardium follows an abnormal fibrofatty deposition, acting as a flawed reparative response [ 123 ].…”
Section: Correlation Of Connexin-43 Expression and Exercise Trainingmentioning
confidence: 99%
“…These data fuel the hypothesis that disruption and rearrangement of the ICD in response to impaired adhesion between cardiomyocytes is a crucial initial step, at least in case of mutations in desmosomal molecules. Other mechanisms described in patients or translational models, such as aberrant WNT or Hippo/YAP signaling, or immune cell infiltrations, 2 , 28 may be secondary responses and in part even represent adaptive attempts to rescue the functional consequences of such severe structural aberrations.…”
Section: Discussionmentioning
confidence: 99%